PENERAPAN METODE QUANTUM TEACHING DALAM PENGAJARAN FIQIH KELAS VIII MTS. MUHAMMADIYAH 31 CUMPLENG, BRONDONG, LAMONGAN TAHUN PELAJARAN 2008/2009: PENERAPAN METODE QUANTUM TEACHING DALAM PENGAJARAN FIQIH KELAS VIII MTS. MUHAMMADIYAH 31 CUMPLENG, BRONDONG, LAMONGAN TAHUN PELAJARAN 2008/2009 - Zunaidah; Bahid Arofat (STAI Muhammadiyah Paciran Lamongan, 2024)
This research is classroom action research which uses descriptive methods. This research is motivated by the low interest and motivation of students to take part in teaching and learning activities which is caused by the use of teaching methods by teachers that do not arouse students' interest, so that this condition affects their learning achievement and creativity. One alternative that can be implemented to overcome this problem is to apply the quantum teaching method in teaching and learning activities. Meanwhile, the subject taken is fiqh, limited to the sub-subject of sacrifice. This research aims to describe teachers' abilities in managing quantum teaching methods, describe student responses to quantum teaching methods and describe student learning outcomes from implementing quantum teaching methods. The benefit of this research is to expand the initial reference for the author so that it can be applied in educational institutions wherever the author teaches, providing feedback for teachers so that it is possible to have good techniques in teaching and can contribute to improving teacher teaching achievement. The subjects of this research were students of class VIII MTs. Muhammadiyah 31 Cumleng, Brondong, Lamongan the pretest results of 66.67%. posttest was 88.89% classical pass.